Functional and clinical characteristics of focal adhesion kinases in cancer progression - Zhang, Zhaoyu; Li, Jinlong; Jiao, Simin; Han, Guangda; Zhu, Jiaming; Liu, Tianzhou (Frontiers in Cell and Developmental Biology, 2022)
Functional and clinical characteristics of focal adhesion kinases in cancer Progression